Convenience and economic benefit of early one-shot Mycoplasma hyopneumoniae vaccination at 3 days of age in a commercial sow farm - Frédéric Vangroenweghe (Journal of Vaccines and Immunology - Peertechz Publications, 2021)
Mycoplasma hyopneumoniae (M. hyopneumoniae) is the primary pathogen of enzootic pneumonia, a chronic respiratory disease in pigs. Vaccination of piglets to protect against M. hyopneumoniae can be performed at several ages, depending on product label specifications. Early intervention in the first week of life may have advantages, since piglets can already become infected with M. hyopneumoniae during the suckling period, resulting in a significant percentage of M. hyopneumoniae-positive piglets around weaning. The current study compared convenience and economic benefits of M. hyopneumoniae vaccination in piglets of 3, 7 and 14 days of age. Duration of piglet vaccination at 3 days of age was significantly (P < 0.05) shorter (2.64 ± 0.08 seconds) as compared to 7 days of age (4.90 ± 0.18 seconds) and 14 days of age (6.04 ± 0.22 seconds). Economic calculation in a 1000-sow unit, using a vaccination convenience calculator, demonstrated that although the total number of piglets vaccinated is lower (- 443 and - 838 at 7 and 14 days of age, respectively) at a later vaccination age, the related increase in vaccine cost in the early vaccination group (Group 1) was largely compensated by the decrease in cost of overall vaccination time (€ 1,115.61 and € 1,461.00 lower at 3 days of age as compared to 7 and 14 days of age, respectively). In conclusion, M. hyopneumoniae vaccination at 3 days of age has several advantages over later vaccination at 7 or 14 days of age. Besides the benefits in convenience of piglet handling at that age, we could also demonstrate economic benefits of early M. hyopneumoniae vaccination.